Droplet CAR-Wash: continuous picoliter-scale immunocapture and washing. Issue 9 (9th April 2019) - Doonan, Steven R.; Lin, Melissa; Bailey, Ryan C.
Abstract : The CAR-Wash provides >100-fold dilution with >98% magnetic bead recovery for washing picoliter-scale droplets at 500 Hz. Abstract : To address current limitations in adapting solid phase sample capture and washing techniques to continuously flowing droplet microfluidics, we have developed the "Coalesce-Attract-Resegment Wash" (CAR-Wash) approach. This module provides efficient, high-throughput magnetic washing by electrocoalescing magnetic bead-laden input droplets with a washing buffer flow and magnetophoretically transporting beads through the buffer into a secondary droplet formation streamline. In this work, we first characterized the technology in terms of throughput, sample retention, and flow-based exclusion of waste volume, demonstrating >500 Hz droplet processing with >98% bead retention and >100-fold dilution in final droplets. Next, we showed that the technique can be adapted to alternative commercially available magnetic beads with lower magnetite content per particle. Then, we demonstrated the CAR-Wash module's effectiveness in washing away a small molecule competitive inhibitor to restore the activity of magnetic bead-immobilized β-galactosidase. Finally, we applied the system to immunomagnetically enrich a green fluorescent protein–histone H2B fusion protein from cell lysate while washing away mCherry and other lysate components. We believe this approach will bridge the gap between powerful biochemical and bioanalytical techniques and current droplet microfluidic capabilities, and we envision future application in droplet-based immunoassays, solid phase extraction, and other complex, multi-step operations.